TEKNOLOGI DALAM PENJAMIN PRODUK HALAL - Susanto, Dedi; Nasrullah bin Sapa; Cut Muthiadin (Sebi : Studi Ekonomi dan Bisnis Islam, 2025)
The halal industry is growing rapidly in line with the increasing demand for halal products, especially in Indonesia. However, the halal assurance process faces challenges in terms of efficiency, transparency, and certification accuracy. This study aims to analyze the role of information technology in accelerating halal certification, identify technologies that improve transparency and efficiency, and examine the challenges of its implementation. This study also explores the potential of technology in supporting Indonesia as a global halal industry hub and formulates strategies to overcome infrastructure, regulatory, and human resource barriers.The method used is a descriptive qualitative approach with literature and case studies. The results show that digital technologies, such as blockchain and the Internet of Things (IoT), can accelerate certification, improve supply chain transparency, and enhance halal production supervision. The main challenges are limited digital infrastructure, low digital literacy in MSMEs, and regulations that do not yet support technology.This study suggests that the government and related institutions provide incentives for MSMEs, improve digital literacy, and develop technology-based halal platforms. With proper support, Indonesia has the potential to become an efficient and transparent global halal industry hub.